-2-6(x-3)=x-4

Simple and best practice solution for -2-6(x-3)=x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-6(x-3)=x-4 equation:


Simplifying
-2 + -6(x + -3) = x + -4

Reorder the terms:
-2 + -6(-3 + x) = x + -4
-2 + (-3 * -6 + x * -6) = x + -4
-2 + (18 + -6x) = x + -4

Combine like terms: -2 + 18 = 16
16 + -6x = x + -4

Reorder the terms:
16 + -6x = -4 + x

Solving
16 + -6x = -4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
16 + -6x + -1x = -4 + x + -1x

Combine like terms: -6x + -1x = -7x
16 + -7x = -4 + x + -1x

Combine like terms: x + -1x = 0
16 + -7x = -4 + 0
16 + -7x = -4

Add '-16' to each side of the equation.
16 + -16 + -7x = -4 + -16

Combine like terms: 16 + -16 = 0
0 + -7x = -4 + -16
-7x = -4 + -16

Combine like terms: -4 + -16 = -20
-7x = -20

Divide each side by '-7'.
x = 2.857142857

Simplifying
x = 2.857142857

See similar equations:

| -14+6n-3+3=5n-6 | | 107=100+x+(19-x) | | 8(t-3)+4t=6(2t+2)-8 | | 5.1(x+3)=20.4 | | 3+8(2k+1)=11+16k | | 9+-3(n-5)=30 | | 18x^2-12x-17=0 | | 8x-3=3x-17 | | 7y+3=-5y-9 | | 3x-8=2(3x-76) | | 17x+5=17x-5 | | Graphy=2x+1 | | -4(3x+9)+3x=6-4(x-3) | | -4x-6y=-18 | | 2piR=x | | 3/5n-4/5=1/5n | | 4(x^3-4X)=0 | | (7rs^2)(-3r^5s^4)= | | 1900-6p=-2(10n+7) | | 6=-12(10n+7) | | 7d-6=22 | | -2v=-6-4t | | A=2x-6 | | 1x+2x=79 | | 4t-8=t-5 | | 2x=5y-108 | | -5(x+3)-(9x-4)=x-5+3 | | x-10+2x-221+0.5x+5=180 | | z(z-3)+2(z+3)=18 | | 5h+4=4h+11 | | w(20w-73)=-63 | | 6(x^2+x-20)=0 |

Equations solver categories